Genome-wide association study of Verticillium longisporum resistance in Brassica genotypes - Wang, Yixiao; Fredua-Agyeman, Rudolph; Yu, Zhiyu; Hwang, Sheau-Fang; Strelkov, Stephen E. (Frontiers in Plant Science, 2024)
Verticillium stripe, caused by Verticillium longisporum, presents an emerging threat to Canadian canola (Brassica napus). Initially detected in Manitoba in 2014, the presence of this pathogen has since been confirmed across western Canada. Infections by V. longisporum can result in yield losses of up to 50%, which is a cause for concern given the susceptibility of most commercial Canadian canola cultivars. The objective of this study was to screen a collection of 211 Brassica genotypes for their reactions to V. longisporum, and to use genome-wide association study (GWAS) to identify single nucleotide polymorphism (SNP) markers for resistance. The plant material consisted of 110 rutabaga (B. napus ssp. napobrassica), 35 canola, 40 Brassica rapa, and 15 Brassica oleracea accessions or cultivars, alongside 11 hosts of the European Clubroot Differential (ECD) set. These materials were screened for resistance under greenhouse conditions and were genotyped using a 19K Brassica SNP array. Three general linear models (GLM), four mixed linear models (MLM), and three GWAS methods were employed to evaluate the markers. Eleven non-commercial Brassica accessions and 9 out of 35 commercial canola cultivars displayed a low normalized area under the disease progress curve (AUDPCnorm.). The non-commercial accessions could prove valuable as potential sources of resistance against V. longisporum. Forty-five SNP markers were identified to be significantly associated with V. longisporum resistance using single-SNP based GWAS analysis. In comparison, haplotype-based GWAS analyses identified 10 to 25 haplotype blocks to be significantly associated with V. longisporum resistance. Between 20% and 56% of QTLs identified by the more conventional single-SNP based GWAS analysis were also detected by the haplotype-based GWAS analysis. The overlapping genomic regions identified by the two GWAS methods present promising hotspots for marker-assisted selection in the future development of Verticillium stripe-resistant canola.